A figurational approach to soft power and sport events. The case of the FIFA World Cup Qatar 2022™ - Næss, Hans Erik (Frontiers in Sports and Active Living, 2023)
Soft power' is a term often used to explain how states seek to be appealing and attractive to others to increase their geopolitical influence instead of using military force or economic threats. As part of a soft power agenda, sport events showcase the values, culture and imagery of a host nation, and through that, ideally, attract investors, tourists and attention. But there are problems with the concept, especially when it is adopted by sport events where it is used as a metaphor, as a heuristic device, and a descriptor of current affairs, to name a few. In particular, the concept does not necessarily capture the accumulation of tit-for-tat strategies and bargaining in geopolitics where sport events are involved. In contrast, by using the FIFA World Cup Qatar 2022™ as key example and drawing upon Norbert Elias' figurational sociology as source of theoretical refinement, this article discusses how soft power can become more precise as an analytical category in a context of sport and geopolitics.